2016
DOI: 10.1038/leu.2016.186
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prior treatment on patients with relapsed multiple myeloma treated with carfilzomib and dexamethasone vs bortezomib and dexamethasone in the phase 3 ENDEAVOR study

Abstract: The randomized phase 3 ENDEAVOR study (N=929) compared carfilzomib and dexamethasone (Kd) with bortezomib and dexamethasone (Vd) in relapsed multiple myeloma (RMM). We performed a subgroup analysis from ENDEAVOR in patients categorized by number of prior lines of therapy or by prior treatment. Median progression-free survival (PFS) for patients with one prior line was 22.2 months for Kd vs 10.1 months for Vd, and median PFS for patients with ⩾2 prior lines was 14.9 months for Kd vs 8.4 months for Vd. For patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 19 publications
2
74
0
1
Order By: Relevance
“…Previous studies have investigated the efficacy of carfilzomib in subgroups of patients categorized by line of therapy and have demonstrated that patients benefit from receiving carfilzomib at first relapse (and this benefit may be greater than that obtained from use of carfilzomib at second or third relapse). In the ENDEAVOR trial, patients who received Kd at first relapse had a median PFS of 22.2 months, while patients who received Kd at second or third relapse had a median PFS of 14.9 months . In comparison with the control arm (Rd), risk of progression or death was reduced by approximately 55% among patients who received carfilzomib at first relapse and by approximately 40% among patients who received carfilzomib at second or third relapse .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have investigated the efficacy of carfilzomib in subgroups of patients categorized by line of therapy and have demonstrated that patients benefit from receiving carfilzomib at first relapse (and this benefit may be greater than that obtained from use of carfilzomib at second or third relapse). In the ENDEAVOR trial, patients who received Kd at first relapse had a median PFS of 22.2 months, while patients who received Kd at second or third relapse had a median PFS of 14.9 months . In comparison with the control arm (Rd), risk of progression or death was reduced by approximately 55% among patients who received carfilzomib at first relapse and by approximately 40% among patients who received carfilzomib at second or third relapse .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the efficacy of carfilzomib in subgroups of patients categorized by number of previous lines of therapy, and among subgroups of patients with or without prior exposure to a proteasome inhibitor. In both ASPIRE and ENDEAVOR, patients who received carfilzomib‐containing regimens had improved median PFS compared with control groups regardless of whether patients were previously exposed to proteasome inhibitors . Additionally, patients who received carfilzomib at first relapse had a significant and clinically relevant improvement in PFS compared with patients who received standard of care at first relapse in both ASPIRE and ENDEAVOR .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In subgroup analyses of ENDEAVOR, for patients receiving carfilzomib plus dexamethasone, median PFS was 8.6 months for patients with lenalidomide-refractory disease and not estimable in those who were not refractory to lenalidomide. In individuals receiving bortezomib plus dexamethasone, median PFS was 6.6 months for patients with lenalidomide-refractory disease and 11.2 months for those who were not refractory to lenalidomide (Moreau et al, 2016c). It must be noted that for both PIs efficacy was greater in patients who were not refractory to lenalidomide than in those with refractory disease.…”
Section: Imid-refractory Diseasementioning
confidence: 99%
“…62 Carfilzomib, ixazomib, and daratumumab combinations are superior whatever the number of lines (1-3). 59,68,69 c The prior use and results of IMIDs and PIs are becoming important issues. Patients with prior treatment are bortezomib-or lenalidomide-exposed; others are bortezomib-or lenalidomide-naive.…”
Section: 55mentioning
confidence: 99%